The causes of dysregulation of immune response in pulmonary tuberculosis: the impact of M. tuberculosis on the course of immune response - I. Ye. Yesimova; O. I. Urazova; V. V. Novitsky; R. R. Hasanova; A. A. Koshkina; Ye. G. Churina (Бюллетень сибирской медицины)
The most plausible formation mechanisms of the secondary immunologic insufficiency and dysregulation of immune response to M. tuberculosis in relation to the biologic specificities of the infectious agent are discussed in this review. The ability of M. tuberculosis to affect the activity of antigen-presenting cells and T-lymphocytes, which manifests itself in disbalance of pro- and anti-inflammatory cytokines and the expression of the basic molecules of intercellular cooperation, the activation of the suppressing mechanisms and apoptosis resulting in immune hypo- and anergy of T-lymphocytes and the disorder of effective immune response formation in general, is also described.